CARS endomicroscopic imaging probe enabled by a double-core double-clad fiber and related focus-combining micro-optical concept - Messerschmidt, Bernhard; Pshenay-Severin, Ekaterina; Matz, Gregor; Reichwald, Karl; Bierlich, Jorg; Kobelke, Jens; Bae, Hyeonsoo; Meyer-Zedler, Tobias; Schmitt, Michael; Popp, Juergen (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2021)
Non-linear endoscopic imaging probes allow for in-vivo, label free tissue histology and thus bring tumour treatment to a new level providing accurate, real time diagnostics. Here we present an endomicroscopic imaging probe for coherent anti-Stokes Raman scattering (CARS) imaging based on a fiber piezo scanner at the distal side of the probe. One of the main hurdles in the implementation of CARS imaging in all-fiber solutions is the generation of a background four-wave-mixing (FWM) signal within the delivery fiber by the Stokes-and pump lasers involved in the process of generation of the nonlinear image. We developed and realised a novel solution based on a silica double-core double-clad (DCDC) fiber, which allows a separate guiding of the exciting Stokes-and pump laser radiation in two separate cores of the delivery fiber. The optical design of the endoscopic probe allows perfect overlap and focusing of the Stokes and pump lasers across the full field of view of the probe.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Endoscopic CARS; Gradient index lens; GRIN lens; Multi-photon micro-endoscopy; Piezo fiber scanner; Silica double-core double-clad (DCDC) fiber